Five Children and It - Edith Nesbit
HENRY BLESH, proprietor of Benezette Hotel, Benezette, was born in Clinton county, Penn., January 14, 1837, a son of John and Elizabeth Blesh. His parents died when he was ten years old, and he was thus early thrown on his own resources. He remained in his native county until 1863, beginning life as a laborer, but later dealt in lumber as a jobber. In 1863 he came to Benezette township and began work in the lumber district and continued that business until 1875 when he bought a hotel in Benezette, and has since had charge of one of the popular resorts for the traveling public in Elk county. He is also engaged in the mercantile business, carrying a complete stock and having a good trade. Mr. Blesh was married in, December, 1865, to Miss Sarah Saltsman, a daughter of Frank and Sarah (Rone) Saltsman, and, they have a family of seven children: Georgia M. (wife of Merrit Jones), Frank, Estella, William H., Bertha, Laura and Emma. Mr. Blesh has held various township offices. He is a member of the Benezette Lodge, No. 988, I.O.O.F.